Auditor Versus Model: Information Choice and Information Processing. - Simnett, Roger; Trotman, Ken (The Accounting Review, 1989)
Abstract ABSTRACT: This paper examines the comparative effect of information choice and information processing on the judgment performance of auditors over two different levels of environmental predictability. The task was the prediction of corporate failure. The study found that information choice, as evidenced through suboptimal selection of ratios, was a limiting factor in performance. However, although subjects were able to utilize all the information from the ratios they selected, they were unable to improve performance when supplied with the superior combination of ratios determined by the environmental model. Thus, information processing also became a limiting factor in performance when subjects were unable to choose their own ratios.